Biometric similarity Test of The Population of T. (Zaria) bantamensis tjicumpaensis with T. (Zaria) javana as a Form of Phylogeny And Evolutionary Proximity - Hita Pandita; Ani Apriani (UIR PRESS, 2021)
Biometric aspects in the Turritellidae family need to be studied as an important identification parameter. Zaria, which is one of the sub genera in the Turritellidae family, deserves to be tested in order to determine the feasibility of the biometric aspect as an identification parameter. This paper aims to provide an overview of the benefits of the biometric aspect as an identification parameter. The method used to re-identify the biometric and morphological aspects of the T. (Zaria) bantamensis tjicumpaensis population with T. (Zaria) javana. The results of the identification were carried out by a T-Test on the biometric aspect to see the similarity of the biometric aspects of the two populations. Based on the results of the T-Test on the parameters of the Wsut: Wang and Wsut: L ratio, it shows that the two Zaria species are the same. Meanwhile, from the morphological aspect, there is a slight difference in the early growth peripherals.